2016
DOI: 10.1063/1.4952961
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural activity shapes the communication and migration patterns in Senegal

Abstract: The communication and migration patterns of a country are shaped by its socioeconomic processes. The economy of Senegal is predominantly rural, as agriculture employs over 70% of the labor force. In this paper, we use mobile phone records to explore the impact of agricultural activity on the communication and mobility patterns of the inhabitants of Senegal. We find two peaks of phone calls activity emerging during the growing season. Moreover, during the harvest period, we detect an increase in the migration f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(1 reference statement)
1
2
0
Order By: Relevance
“…In this work, we study the communication patterns of the country of Senegal and explore their correlations with underlying real world structures and dynamics. Our findings [1] show that agricultural activities have a key role in shaping the phenomena recorded in the data. Another important factor would be the traditional religious festivities.…”
supporting
confidence: 52%
“…In this work, we study the communication patterns of the country of Senegal and explore their correlations with underlying real world structures and dynamics. Our findings [1] show that agricultural activities have a key role in shaping the phenomena recorded in the data. Another important factor would be the traditional religious festivities.…”
supporting
confidence: 52%
“…S6). Overall mobility displays clear weekly patterns (especially in the most urbanized regions, such as Dakar), longer-term trends (possibly linked to seasonal economic activities, such as agriculture and fishing) and sudden pulses 46 . Religious gatherings attract pilgrims from all regions of Senegal and thus produce remarkable mobility fluxes, with the temporary displacement of hundreds of thousands of people, like in the case of the Grand Magal de Touba and Kazu Rajab (also held in Touba).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that poverty levels and productivity in groundnut producing areas are relatively more vulnerable to rainfall fluctuations than elsewhere in Senegal (e.g. Cabral 2012), and that patterns of labour migration to and from the groundnut basin are still closely timed around seasonal rainfall variations (Martin-Gutierrez et al 2016;Hummel 2016).…”
Section: Latent Surplus Populations and Groundnut Production Over The Long Runmentioning
confidence: 99%